2021
DOI: 10.1002/bit.27980
|View full text |Cite
|
Sign up to set email alerts
|

A transfer learning approach for predictive modeling of bioprocesses using small data

Abstract: Predictive modeling of new biochemical systems with small data is a great challenge.To fill this gap, transfer learning, a subdomain of machine learning that serves to transfer knowledge from a generalized model to a more domain-specific model, provides a promising solution. While transfer learning has been used in natural language processing, image analysis, and chemical engineering fault detection, its application within biochemical engineering has not been systematically explored. In this study, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They argued that the performance gains obtained through transferring learning techniques can improve the application of computer‐aided diagnoses in various conditions. Generally, the performance of CNN models improves as the number of datasets increases 23 . However, in the field of medical imaging, annotating a large number of medical images is still challenging and time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that the performance gains obtained through transferring learning techniques can improve the application of computer‐aided diagnoses in various conditions. Generally, the performance of CNN models improves as the number of datasets increases 23 . However, in the field of medical imaging, annotating a large number of medical images is still challenging and time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the performance of CNN models improves as the number of datasets increases. 23 However, in the field of medical imaging, annotating a large number of medical images is still challenging and time-consuming. Although dozens or hundreds of GBM datasets comprising patient information and complete labels provide significant amounts of data, in terms of CNN model training, they are still considered small, which may lead to overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 105 gliomas by Peng et al (2021), the AUC and accuracy of classifying IDH status by the Lasso method were 0.770 and 0.823. In general, the performance of the model increases with the size of the dataset (Rogers et al, 2022). However, even in a large cohort, the classification results obtained with a single algorithm are still unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al. investigated 357 glioma patients by using Bayesian neural networks and integrated radiomics features from Gd‐T1 and ADC; the AUC, accuracy, sensitivity, and specificity for predicting TERT mutations were 0.598, 0.685, 0.976, and 0.290, respectively (Rogers et al., 2022 ). In this regard, it is very important to use appropriate algorithms to build the effectiveness model.…”
Section: Discussionmentioning
confidence: 99%
“…It would enable the utilization of biological data published in the literature and reduce the demand for data collection when investigating new processes. Rogers et al ( 55 ) showed that transfer learning is a highly data-efficient technique to predict the modeling of bioprocesses, a typically low-dimensional, small-data problem, but its usage in the biomedical field is scarce. In the present study, we will extract generalizable knowledge from well-understood published biological data, capturing essential process mechanisms to set a source model.…”
Section: Discussionmentioning
confidence: 99%